The Influence of Competency, Independence, Professional Skepticism on Fraud Detection on Financial Statements in The Regional Government of West Java Province - Gusti Bara Tarimushela; Emilia Tri Tani; Rita Yuniarti (Eduvest - Journal of Universal Studies, 2024)
The research aims to determine the influence of competence, independence and skepticism on fraud detection. The research method used was explanatory research, the research population was active auditors/examiners at the BPK RI Representative of West Java Province with a sample size of 80 people. The analysis used uses multiple linear regression tests, coefficient of determination tests and hypothesis tests. The research results show that examiner competency influences fraud detection in local government financial reports which shows that the examiner has good competence. The independence of examiners influences fraud detection in regional government financial reports. This shows that the independence of auditors at BPK RI West Java Province Representative is considered good but needs to be improved to be better. The professional skepticism of auditors in conducting audits influences fraud detection in regional government financial reports which are assessed. Good, although it still needs to be improved to be better.